2002
DOI: 10.1016/s1053-8119(02)91154-7
|View full text |Cite
|
Sign up to set email alerts
|

Bach Speaks: A Cortical “Language-Network” Serves the Processing of Music

Abstract: The aim of the present study was the investigation of neural correlates of music processing with fMRI. Chord sequences were presented to the participants, infrequently containing unexpected musical events. These events activated the areas of Broca and Wernicke, the superior temporal sulcus, Heschl's gyrus, both planum polare and planum temporale, as well as the anterior superior insular cortices. Some of these brain structures have previously been shown to be involved in music processing, but the cortical netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
180
3
11

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(218 citation statements)
references
References 64 publications
24
180
3
11
Order By: Relevance
“…This finding was taken to indicate that the neural mechanisms underlying the generation of the P600 are not only activated by the processing of language, but also by the processing of music (Patel et al, 1998;Patel, 1998). With respect of similarities between music and language processing, it is interesting to note that the hypothesis of shared neural circuits underlying the generation of music-and language-related ERP components such as ERAN/ELAN, or P600, is supported by the findings that brain structures involved in the processing of language also play an important role for the processing of music (Platel et al, 1997;Liegeois-Chauvel et al, 1998;Peretz et al, 1994;Zatorre et al, 1994;Wallin et al, 2000;Maess et al, 2001;Koelsch et al, 2000a).…”
Section: Discussionmentioning
confidence: 99%
“…This finding was taken to indicate that the neural mechanisms underlying the generation of the P600 are not only activated by the processing of language, but also by the processing of music (Patel et al, 1998;Patel, 1998). With respect of similarities between music and language processing, it is interesting to note that the hypothesis of shared neural circuits underlying the generation of music-and language-related ERP components such as ERAN/ELAN, or P600, is supported by the findings that brain structures involved in the processing of language also play an important role for the processing of music (Platel et al, 1997;Liegeois-Chauvel et al, 1998;Peretz et al, 1994;Zatorre et al, 1994;Wallin et al, 2000;Maess et al, 2001;Koelsch et al, 2000a).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, Broca's aphasia can be understood in terms of difficulties with certain aspects of temporal processing or on-line integration of information. Furthermore, several recent studies have shown that the left inferior frontal region has a broader role in cognition than just language (Hagoort, 2005;Marcus, Vouloumanos, & Sag, 2003), including musical syntax (e.g., Koelsch et al, 2002;Maess, Koelsch, Gunter, & Friederici, 2001) and visuo-spatial sequence processing (Bahlmann, Schubotz, Mueller, Koester, & Friederici, in press). Thus, next to evidence from a study on aphasic patients (Patel, Iversen, Wassenaar, & Hagoort, 2008), a growing body of evidence from functional neuroimaging suggests an overlap in the processing of structural relations in language and music (for a review see Patel, 2003).…”
Section: Dynamic Functional Modularity and The Role Of The Left Infermentioning
confidence: 99%
“…Regarding the core common areas, engagement of similar areas for language and music is reasonable to be expected since, after all, music processing shares some circuitry with spoken language processing, especially when subjects are experts in both music and language systems (Koelsch, Gunter, von Cramon, Zysset, & Lohmann, 2002;Patel, Gibson, Ratner, Besson, & Holcomb, 1998;Patel, 2003;Steinbeis & Koelsch, 2008).…”
Section: Neuroimaging Studies Of Music-related Working Memorymentioning
confidence: 99%